Case report of immune checkpoint inhibitor induced cholestatic hepatitis, acute renal injury and asymptomatic pancreatic enzyme elevation simultaneously - Jiao, Rui; Wang, Chenyu; Ying, Hongyan; Nie, Muwen; Leng, Jing; Liu, Yuan; Zhang, Zhiyang; Zhou, Na; Bai, Chunmei (Frontiers in Immunology, 2025)
BackgroundImmune checkpoint inhibitors (ICIs) have demonstrated promising antitumor activity. However, it may induce immune-related adverse events (irAEs). Multi-organ irAEs remain heterogeneous and incompletely characterized. We report a unique irAE pattern with synchronous hepatic, renal and pancreatic involvement which is first reported.Case presentation5 males developed a rare multi-organ irAE pattern with concurrent cholestatic hepatitis, renal injury and pancreatic enzyme elevation, representing 0.40% of the ICI-treated cohort. The syndrome showed early, rapidly onset and often began with nonspecific complaints requiring close monitoring.ManagementResponses of high dose glucocorticoid were varied by organs. Compared with renal and pancreatic injury, cholestatic hepatitis was less responsive to steroids. Out of 3 cases who were refractory to steroids, 2 cases were given artificial liver treatment and 1 case was given bilirubin adsorption after steroid failure.OutcomesImmunosuppression by standard glucocorticoid showed limited efficacy in cholestatic hepatitis. The 2 patients received artificial liver support improved biochemically, while bilirubin adsorption alone provided only transient reduction of bilirubin in one case. As for final clinical outcome, one patient died from severe infection during therapy agianst irAE; one patient died from cancer progression despite irAE recovery; and the others achieved full recovery from this irAE combination.